Pertuzumab plus trastuzumab in combination with standard neoadjuvant anthracycline-containing and anthracycline-free chemotherapy regimens in patients with HER2-positive early breast cancer: a randomized phase II cardiac safety study (TRYPHAENA) - Schneeweiss, Andreas; Chia, S.; Hickish, T.; Harvey, V.; Eniu, A.; Hegg, R.; Tausch, C.; Seo, J. H.; Tsai, Y. -F.; Ratnayake, J.; McNally, V.; Ross, G.; et al. (Annals of oncology, 2013)
Background - Pertuzumab (P) combined with trastuzumab (H)-based chemotherapy improves efficacy in early and advanced HER2-positive breast cancer. We assessed the tolerability, with particular focus on cardiac safety, of H and P with chemotherapy in the neoadjuvant treatment of HER2-positive early breast cancer. - Patients and methods - In this multicenter, open-label phase II study, patients with operable, locally advanced, or inflammatory breast cancer were randomized 1 : 1 : 1 to receive six neoadjuvant cycles q3w (Arm A: 5-fluorouracil, epirubicin, cyclophosphamide [FEC] + H + P ×3 → docetaxel [T] + H + P ×3; Arm B: FEC ×3 → T + H + P ×3; Arm C: T + carboplatin + H [TCH]+P ×6). pCR was assessed at surgery and adjuvant therapy given to complete 1 year of H. - Results - Two hundred twenty-five patients were randomized. During neoadjuvant treatment, two patients (2.7%; Arm B) experienced symptomatic left ventricular systolic dysfunction (LVSD) and 11 patients (Arm A: 4 [5.6%]; Arm B: 4 [5.3%]; Arm C: 3 [3.9%]) had declines in left ventricular ejection fraction of ≥10% points from baseline to <50%. Diarrhea was the most common adverse event. pCR (ypT0/is) was reported for 61.6% (Arm A), 57.3% (Arm B), and 66.2% (Arm C) of patients. - Conclusion - The combination of P with H and standard chemotherapy resulted in low rates of symptomatic LVSD.